Penerapan Media Gambar dalam Meningkatkan Kemampuan Menulis Siswa Kelas IV B SDN Inpres 145 Pampangan - Sri Rahayu; Nhabila Putri; Raudah Nailati; Nurul Qalbi Ahmad (Asosiasi Riset Ilmu Pendidikan Indonesia, 2023)
This research aims to answer the problems that have been raised/explained above, while the aim of this research is to describe the improvement in learning outcomes using the inquiry learning model with the help of image media in Class IV B SDN 145 Inpres Pampangan. In the P2K implementation carried out at SDN 145 Inpres Pampangan, the research subjects were 28 Class IV B students at SDN 145 Inpres Pampangan, of which the total number of students was 16 women and 12 men. This was carried out in 2 cycles, the first cycle had 3 meetings and the second cycle had 3 meetings. Evaluation in class is carried out in the form of questions and evaluation questions. During the learning process, there is a change in students' attitudes during the learning process in accordance with the results of observations, namely by implementing the guided inquiry learning model assisted by image media, it can increase students' self-confidence to ask both the teacher and their friends about material they do not understand and can increase student attendance. .Data collection was carried out through observing teacher activities and observing student activities. The number of students is 28 people; The results of initial observations made in cycle I were only 62%, increasing to 82% in cycle II. With this increase, it can be concluded that the application of image media can improve the writing skills of grade 4 students at SDN 145 Inpres Pampangan.